National and International Library Collaboration: Necessity, Advantages - Mark, Timothy (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2007)
The advantages of cooperation between research library associations can be demonstrated quite clearly. Where cooperation becomes essential is where there is a common cause to champion or an initiative to pursue for the common good. Thanks in part to the power of information communications technology, research is becoming increasingly international in scope. The members of interdisciplinary and multidisciplinary research teams are frequently drawn from across the world. Correspondingly, scholarly publishing (especially in medicine and the sciences) is dominated by a few multinational publishers. In this context, issues that play a vital role in global scholarly communication - such as copyright, journal pricing, the managing of datasets, digital preservation and open access - are issues for the research library community everywhere in the world. Certainly there are many challenges at the local or regional level. However there are definite roles that research library associations can play most effectively at the national or international level. It is clear that by sharing expertise, building partnerships and alliances, it is possible to address common issues much more effectively than when working alone. What is special is that potentially the most powerful form of cooperation is advocacy at the national and international levels. It is essential for research library associations to work together at the political level to move their agenda forward. Examples are lobbying about copyright legislation (nationally, or within the EC or at WIPO); or promoting the cause of Open Access. The unique value of LIBER is to provide a forum and a platform for European research library associations to explore and benefit from cooperation and their shared strength.